Profound dysregulation of T cell homeostasis and function in patients with severe COVID‐19. Issue 9 (30th June 2021) - Adamo, Sarah; Chevrier, Stéphane; Cervia, Carlo; Zurbuchen, Yves; Raeber, Miro E.; Yang, Liliane; Sivapatham, Sujana; Jacobs, Andrea; Baechli, Esther; Rudiger, Alain; Stüssi‐Helbling, Melina; Huber, Lars C.; et al.
Abstract: Background: Coronavirus disease 2019 (COVID‐19) is caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and shows a broad clinical presentation ranging from asymptomatic infection to fatal disease. A very prominent feature associated with severe COVID‐19 is T cell lymphopenia. However, homeostatic and functional properties of T cells are ill‐defined in COVID‐19. Methods: We prospectively enrolled individuals with mild and severe COVID‐19 into our multicenter cohort and performed a cross‐sectional analysis of phenotypic and functional characteristics of T cells using 40‐parameter mass cytometry, flow cytometry, targeted proteomics, and functional assays. Results: Compared with mild disease, we observed strong perturbations of peripheral T cell homeostasis and function in severe COVID‐19. Individuals with severe COVID‐19 showed T cell lymphopenia and redistribution of T cell populations, including loss of naïve T cells, skewing toward CD4 + T follicular helper cells and cytotoxic CD4 + T cells, and expansion of activated and exhausted T cells. Extensive T cell apoptosis was particularly evident with severe disease and T cell lymphopenia, which in turn was accompanied by impaired T cell responses to several common viral antigens. Patients with severe disease showed elevated interleukin‐7 and increased T cell proliferation. Furthermore, patients sampled at late time points after symptom onset had higher T cell counts and improved antiviral T cell responses. Conclusion: Our study suggests that severe COVID‐19 is characterized by extensive T cell dysfunction and T cell apoptosis, which is associated with signs of homeostatic T cell proliferation and T cell recovery. Abstract : In severe COVID‐19 T cell populations show perturbations, including loss of naïve T cells, CD4 + T cell skewing toward T follicular helper and cytotoxic phenotypes and expansion of activated and exhausted T cells. Apoptosis and migration contribute to the lymphopenia of severe disease, which is accompanied by Interleukin‐7 elevation. Functional responses to viral antigens are reduced in severe COVID‐19. Abbreviations: COVID‐19, coronavirus disease 2019; CyTOF, cytometry by time‐of‐flight; TFH, T follicular helper cell